Determinants of investment in private residential construction in the Philippines - Novero, Vicente Louise C.; Desilos, Darwin D.
The housing problem in the Philippines has worsened over the years as evidenced by the widening gap between the people's housing needs and supply. Housing investment failed to close in the gap as it competes with other sectors of the economy with the use of available resources. Investment financing, unlike needs, are limited. The paper looked into the production side of the housing economy and examined various economic and demographic determinants of investment in private residential housing (value of private residential construction started as percentage of gross domestic product) in the Philippines, reporting data for the period 1970 to 2013. Development level (gross domestic product per capita) and general price level (inflation rate) may be regarded as the variables measuring demand for housing investment; Population growth (population growth rate and degree of urbanization (urban-rural ration) as variables measuring need for shelter. Backward elimination was used to determine the least number of variables that would still explain a percentage of variance in the dependent variable that was comparable to the percentage explained with all the variables in the equation. After several significance tests and regression diagnostics, a time-series linear regression established that the degree of urbanization could statistically significantly predict the square root transformation of share of residential housing in total economic output, F(1,42)=46.08, p=2.92E-08, 52.31% of the explained variability and elasticity of 10.879. The regression equation was √[-0.079+0.039(X)]. Result of this study suggests use of population trend, particularly urban migration, on policy formutation concerning housing investment.